Prevalence and factors associated with teenage pregnancy in refugee settlements of northern Uganda post-COVID-19 (2020–2023): a cross-sectional study - Felix Bongomin; Donald Otika; George Odongo; Ruth Mary Mary Muzaki; Beatrice Oweka Lamwaka; Francis Pebalo Pebolo (BMJ Open)
Background Following the COVID-19 pandemic, there was an increase in teenage pregnancies nationally, however, limited data exists regarding the same among girls living in refugee settlements.Objectives We evaluated the prevalence of teenage pregnancy and associated factors in Palorinya and Bidi Bidi refugee settlements in Obongi and Yumbe districts of northern Uganda, in the post-COVID-19 era.Design We conducted a cross-sectional study.Setting Refugee settlements in northern Uganda.Participants We included 385 teenage girls aged 15–19 years.Methods We used convenience sampling techniques between March and May 2023. Prevalence of teenage pregnancy was assessed by self-reported pregnancies between January 2020 and May 2023 among participants. We conducted Pearson’s χ2 and Fisher’s exact tests for bivariate analysis. All variables with a p value<0.2 at bivariate analysis were included in multivariable regression. We applied a modified Poisson regression model at the multivariable level to evaluate independent associations. The level of statistical significance was set at p<0.05.Primary and secondary outcome measures The primary outcome measure was the prevalence of teenage pregnancy, assessed through self-reported pregnancies among participants. Secondary outcome measures included factors associated with teenage pregnancy, such as living with a husband, lack of formal education, peer pressure and history of sexual abuse.Results Overall, the mean age was 17 (IQR: 15–18), and sexual debut was at 16 (IQR: 15–17) years. Lifetime modern contraceptive use was 13.8% (n=53/385) and current use was 7.5% (n=29/385). Teenage pregnancy period prevalence was 34.0% (CI: 29.4% to 38.9%). Factors independently associated with teenage pregnancy were: living with a husband (aPR: 3.8, 95% CI: 2.51 to 5.84, p<0.001), lack of formal education (Adjusted Prevalence Ratios - aPR: 2.3, 95% CI: 1.26 to 4.35, p=0.007), peer pressure (aPR: 2.1, 95% CI: 1.54 to 2.86, p<0.001) and history of sexual abuse (aPR: 1.5, 95% CI: 1.07 to 1.99, p=0.018).Conclusion Our study revealed that around 1 in 3 adolescent girls in northern Uganda’s refugee settlements experienced pregnancy during the COVID-19 pandemic, with only 1 in 13 currently using modern contraceptives. To address this, targeted strategies by relevant authorities are crucial, including legal actions against sexual abuse, promoting girl child education and enhancing access to long-term contraception to reduce teenage pregnancy and associated health risks in these settings.